2010
DOI: 10.1111/j.1469-7998.2010.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple morphological characters needed for field identification of cryptic long‐eared bat species around the Swiss Alps

Abstract: The identification of cryptic species may significantly change our view about their distribution, abundance, ecology and therefore conservation status. In the European Alps, molecular studies have revealed the existence of three sibling species of plecotine bats Plecotus auritus, Plecotus austriacus and, very recently, Plecotus macrobullaris. Knowledge of the ecological niche partitioning of cryptic species is a requisite to develop sound conservation policies. Yet, this requests the development of unambiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 25 publications
0
38
1
Order By: Relevance
“…All sites were already known as relatively large maternal colonies (20-40 females) from a previous study (Ashrafi et al 2010). Faecal samples were obtained from bats mist-netted at the entrance of their attic roost-to minimise disturbance of the colony -when returning from their nocturnal foraging.…”
Section: Field Sampling and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…All sites were already known as relatively large maternal colonies (20-40 females) from a previous study (Ashrafi et al 2010). Faecal samples were obtained from bats mist-netted at the entrance of their attic roost-to minimise disturbance of the colony -when returning from their nocturnal foraging.…”
Section: Field Sampling and Data Collectionmentioning
confidence: 99%
“…Faecal samples were obtained from bats mist-netted at the entrance of their attic roost-to minimise disturbance of the colony -when returning from their nocturnal foraging. For each roost, the species" identity had been previously assessed (in 2006) by DNA analysis of several individuals in each roost (Ashrafi et al 2010). During the present study, we further identified individuals based on eight external characters, as suggested by Ashrafi et al (2010).…”
Section: Field Sampling and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plecotus species are overall very similar to each other, which makes their field identification extremely complex and sometimes impossible. In particular, their biometric characteristics greatly overlap between species, and the lack of easily recognizable morphological characters (Ashrafi et al 2010, Tvrtkovic et al 2005, strongly suggests that genetic analyses need to be performed in order to correctly identify the various species, especially outside their common distribution range (Alberdi et al 2016). The identification uncertainty is the basis for the scarcity of circumstantiated records of Plecotus macrobullaris, and as a result, its conservation status is Data Deficient (DD) in the Italian Red List of Mammals (Rondinini et al 2013).…”
Section: Plecotus Macrobullarismentioning
confidence: 99%